If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3y + -1) = 5y + 11 Reorder the terms: 4(-1 + 3y) = 5y + 11 (-1 * 4 + 3y * 4) = 5y + 11 (-4 + 12y) = 5y + 11 Reorder the terms: -4 + 12y = 11 + 5y Solving -4 + 12y = 11 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. -4 + 12y + -5y = 11 + 5y + -5y Combine like terms: 12y + -5y = 7y -4 + 7y = 11 + 5y + -5y Combine like terms: 5y + -5y = 0 -4 + 7y = 11 + 0 -4 + 7y = 11 Add '4' to each side of the equation. -4 + 4 + 7y = 11 + 4 Combine like terms: -4 + 4 = 0 0 + 7y = 11 + 4 7y = 11 + 4 Combine like terms: 11 + 4 = 15 7y = 15 Divide each side by '7'. y = 2.142857143 Simplifying y = 2.142857143
| a^2+18a+81= | | 18-k=9 | | s=6r+ph | | 1+2x=4(x+2)-3(x-3) | | -2(-2-2.66y)-5y=3 | | 4(3y-1)=5x-11 | | 9y^2+9y-10= | | 18-4x+8x=-2(-8x+9) | | 30x=4(3a+5)-7a | | -3x+7(7x-5)=195 | | =ab+8x+2b+16 | | 5(2x+5)=-11 | | 8y+16-8y=-3 | | Y^2=52 | | z-4=2 | | 4(3y-1)=6x+10 | | -x-3x-5x=-49 | | 6x-18=9x+9 | | x+8=(-7)+4x | | 0.6(x+0.4)=0.8(x-4.2) | | 16-j=9 | | 3x=16.8 | | 8+x=-23 | | -1t=14 | | -(x+2)+5=7x+3-8x | | 18(2x-5)=5(x-4) | | 4(2.5x-2)=2(x-4)+x+13 | | 17-c=8 | | .8x-1=-5 | | 27=-2(2x+8) | | -3x-8(x+9)=-5(2x+3) | | 7x-20=-(-6) |